Dark places [videorecording (DVD)] - Paquet-Brenner, Gilles; Theron, Charlize; Moretz, Chloë, 1997-; Hoult, Nicholas, 1989-; Flynn, Gillian, 1971- (Lionsgate, 2015)
Libby Day was only seven years old when her mother and two sisters were murdered and her brother Ben was jailed for the crime. Now, twenty-five years later, Libby discovers shocking evidence that Ben may be innocent, and the real killer still at large.